2019
DOI: 10.1111/roie.12408
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility, vertical product differentiation and international competition

Abstract: Would a foreign firm's consumer-oriented corporate social responsibility (CSR) activities be rewarded by an importing country's voluntary tariff reduction? The current paper addresses this question in an import-competing duopoly model with vertical product differentiation. It is shown that the tariff will decrease if the foreign firm switches from a purely profit-driven firm to a CSR firm. A consumer-oriented CSR strategy will always hurt the domestic firm's profit, whereas the relationship between the foreign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…CSR strategies of foreign firms will have an important impact on the government's trade policy (Manasakis et al, 2018). L. F. S. Wang et al (2012) and Li et al (2019) found that the tariff rate will decrease if the foreign firm switches from a purely profit-driven firm to a CSR firm, while Y. M. Chang et al (2014) demonstrated that when only the foreign exporting firm launches its consumer-oriented CSR, the optimal tariff rate set by the domestic government is strictly higher than the situation where the foreign firm is a purely profit-maximizing exporter. The difference between the results of L. F. S. Wang et al (2012) and Y. M. Chang et al (2014) is mainly due to the different market structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CSR strategies of foreign firms will have an important impact on the government's trade policy (Manasakis et al, 2018). L. F. S. Wang et al (2012) and Li et al (2019) found that the tariff rate will decrease if the foreign firm switches from a purely profit-driven firm to a CSR firm, while Y. M. Chang et al (2014) demonstrated that when only the foreign exporting firm launches its consumer-oriented CSR, the optimal tariff rate set by the domestic government is strictly higher than the situation where the foreign firm is a purely profit-maximizing exporter. The difference between the results of L. F. S. Wang et al (2012) and Y. M. Chang et al (2014) is mainly due to the different market structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Panasonic and Honda have organized afforestation activities in China; Dell donates computers to Chinese high schools. In order to gain a larger market share, many foreign firms may initially include consumer surplus in their decision‐making goals (Y. M. Chang et al., 2014; Li et al., 2019; L. F. S. Wang et al., 2012). Adopting corporate social responsibility (CSR) can make firms better recognized by domestic consumers and be regarded as a competitive strategy (Gazzola & Colombo, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation